The effect of using the flexible group’s strategy according to the sense of movement exercises in learning some football and basketball skills - Amir Ismail, Saad; Toma Radi, Emad; Ali Hussein, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The research included the definition of the research, the introduction, and the importance of the research, which is that the teacher who is fluent in using different strategies and methods during teaching is the one who makes the lesson characterized by the flexibility and vitality that it produces. In his own style, which is reflected on the learners and makes them interact with the lesson through good performance of the exercise and outputs the educational unit in a manner consistent with the level and capabilities of the learners, which in turn gives an advantage in learning those mathematical skills? Football and basketball, which is one of the group games that are characterized by a lot of interest in the teammate, the opponent, and the ball, as well as a somewhat high degree of movement, skill, and physical abilities with friction with the opponent’s team and thus require complex exercises, especially in terms of feeling and perception of distance and time. The teacher uses the flexible group strategy by teaching and introducing movement perceptions of movement that develop the learner’s abilities in football and basketball and its effect on motivation and learning skills. As for the research problem, it lies in the fact that researchers, through their work as teachers and their field trips to schools during application periods, the teaching staff who have studied physical education lack the change and recognition of what is modern in teaching. Methods of strategies and methods as well as students’ weakness in terms of perception and sense of movement and learning, which prompted researchers to find out this real problem, study it, and provide a solution for that, by using a flexible group strategy according to perception and movement exercises in learning some skills in football and basketball. The objectives included-Preparing educational units using the strategy of flexible groups according to training, perception and movement to learn some skills in football and basketballKnowing the effect of using the flexible group strategy according to training, perceptual kinesthetic, on learning some skills in football and basketball. And that the research method, which is the experimental and eloquent curriculum, which consisted of 60 students in the preparatory stage of literary fifth grade, also included the tests used in the research, the exploratory experiment, the preliminary tests, the application of the educational units to the research sample and the post-tests, and the presentation, analysis and discussion of the results prior to And a posture between the two experimental groups. Control and post-dimensional tests between the two groups in skills. As for the findings of the researchers, namely. The results showed the superiority of the experimental group that used the flexible group strategy according to training, perception, and movement in learning some skills in football and basketball over the control group in football and basketball.